A Straightforward Selective Acylation of Phenols over ZSM-5 towards Making Paracetamol Precursors - Robby Roswanda; Alfhons Daniel Sirampun; Rino Rakhmata Mukti; Didin Mujahidin (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2018)
Commercially available ZSM-5 was minimally treated as the catalyst to selectively acylate phenols. The ZSM-5 was simply immersed in ammonium nitrate in order to fill the pores with Brönsted acid to concentrate the catalytic reactions inside the pores. The reactions were carried out in liquid phase at 383 K. Acetic acid and propionic acid were chosen as the acyl substrate. Gas chromatography reveals two products which are phenyl acetate and almost exclusively para-hydroxyacetophenone meaning no ortho product observed. This para selectivity can be attributed to the pores of ZSM-5 where the reaction is assumed to be happening via intermolecular reaction. It is a relatively straightforward method in making para-hydroxyacetophenone which is known as paracetamol precursor.